Influence of a Paleosedimentary Environment on Shale Oil Enrichment: A Case Study on the Shahejie Formation of Raoyang Sag, Bohai Bay Basin, China - Wei, Yongbo; Li, Xiaoyan; Zhang, Ruifeng; Li, Xiaodong; Lu, Shuangfang; Qiu, Yan; Jiang, Tao; Gao, Yuan; Zhao, Tiedong; Song, Zhaojing; Zhao, Meihong (Frontiers in Earth Science, 2021)
The characteristics of paleosedimentary environments are of great significance for the enrichment of organic matter (OM) and hydrocarbons in lacustrine shale. This study analyzed mineralogy, well logging data, organic geochemical parameters (total organic carbon and pyrolyzed hydrocarbon), inorganic geochemical parameters (major and trace elements), and multiple geochemical proxies based on inorganic geochemical parameters. These were used to reconstruct the paleosedimentary environment of the lower 1st Member of the Shahejie Formation (Es1L) to reveal OM and shale oil enrichment mechanisms and establish a shale oil enrichment model. The (Fe2O3+Al2O3)/(CaO + MgO), Sr/Ba, Rb/Sr, Cu/Al, and Th/U parameters indicate that the Es1L in Raoyang Sag was deposited in a paleoenvironment dominated by arid paleoclimate, reducing conditions, and saltwater. Paleoclimate, clastic influx intensity, preservation conditions, paleoproductivity, and paleosalinity all affect OM abundance. The OM accumulation in the shale of Es1L was mainly controlled by the high primary productivity of surface water due to algal blooms and moderate salinities, which was achieved using stratified water columns with low oxygen conditions in bottom water. As the main valuable sites for shale oil storage, carbonate mineral depositions are of great significance for oil enrichment. As the dominant lithofacies for oil enrichment, carbonate-rich shale and calcareous shale lithofacies were deposited under a drier paleoclimate, low clastic influx intensity, strong reducing conditions, high paleoproductivity, and moderate salinity paleoenvironment. Additionally, the profile of the shale oil sweet spot was determined through the combination of lithofacies, logging, and paleosedimentary environment data.